2017
DOI: 10.1080/14606925.2017.1352714
|View full text |Cite
|
Sign up to set email alerts
|

The Speedcycle: a design-led framework for fast and slow circular fashion lifecycles

Abstract: This paper reviews a project within the multi-disciplinary Mistra Future Fashion research programme (2015-2019) which aims to provide guidelines for designers to better design circular fashion products for 'appropriate speeds'. Researchers at UAL have been exploring the seemingly opposed approaches to fast and slow 'fashion speeds' through a literature and practice review, alongside workshops with industry and emerging designers to better understand the challenges for designers. In this paper the author review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 1 publication
0
25
0
Order By: Relevance
“…Cong et al [80] suggested a method to improve end-of-use product recyclability through a sequence of steps that evaluate various end-of-use scenarios and then analytically define which components of a product are more suitable to be disassembled, recycled, and reused. Goldsworthy [83] proposed to take into account the multiple rhythms and speeds (e.g., slow and fast fashion speed) within a product's entire lifecycle in order to design effective circular fashion products. For example, extending the lifetime of a "fast product" might not necessarily be more sustainable if it comes at the cost of recyclability, or if durability is achieved through material features that require care and laundry with higher environmental impacts.…”
Section: Design For Circular Production Processesmentioning
confidence: 99%
“…Cong et al [80] suggested a method to improve end-of-use product recyclability through a sequence of steps that evaluate various end-of-use scenarios and then analytically define which components of a product are more suitable to be disassembled, recycled, and reused. Goldsworthy [83] proposed to take into account the multiple rhythms and speeds (e.g., slow and fast fashion speed) within a product's entire lifecycle in order to design effective circular fashion products. For example, extending the lifetime of a "fast product" might not necessarily be more sustainable if it comes at the cost of recyclability, or if durability is achieved through material features that require care and laundry with higher environmental impacts.…”
Section: Design For Circular Production Processesmentioning
confidence: 99%
“…Mestre and Cooper, 2017;den Hollander, Bakker and Hultink, 2017) including in the fashion and textile industry which has begun re-using materials that were often recycled (e.g. Moorhouse and Moorhouse, 2017;Smith, Baille and McHattie, 2017;Goldsworthy, 2017). Various authors highlight that designers need to change their thinking and consider the whole lifecycle of products before even starting to design (Andrews, 2015;Ceschin and Gaziulusoy, 2016; European Environment Agency, 2017).…”
Section: Global Complexities: China's Changing Waste Acceptance Policymentioning
confidence: 99%
“…Early analysis of life-cycle thinking resulted in a visualisation tool named the "Speed Cycle" (Goldsworthy, 2017), which showed that the same impact savings might theoretically be possible through reducing production impacts as for increasing garment usage. i.e.…”
Section: Reducing Production Impactsmentioning
confidence: 99%